The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00246-007-9127-6
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Plastic Bronchitis Presenting 9 Years After Fontan

Abstract: A 15-year-old boy with hypoplastic left heart syndrome experienced plastic bronchitis 9 years after completion of a nonfenestrated lateral tunnel Fontan. Despite cardiac catheterization with coil embolization of collateral vessels and initiation of a pulmonary toilet regimen, including aerosolized tissue plasminogen activator, he continued to expectorate large acellular-mucinous casts. Finally, after optimization of cardiac function with the addition of carvedilol, the expectorated casts decreased in number. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…At present, inhaled tPA is anecdotally used to treat PB [7, 9, 28, 29]. In this study we showed that tPA, in amounts derived from experimental models, was effective in reducing cast mass ex vivo [10, 15, 25].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…At present, inhaled tPA is anecdotally used to treat PB [7, 9, 28, 29]. In this study we showed that tPA, in amounts derived from experimental models, was effective in reducing cast mass ex vivo [10, 15, 25].…”
Section: Discussionmentioning
confidence: 95%
“…Plastic bronchitis (PB) is a rare, primarily pediatric disease that may be a complication of congenital heart disease (CHD) or its surgical palliation by the Fontan procedure [7, 9, 12, 13, 16, 21, 29]. The hallmark of PB, is the formation of rubbery “casts” in the airway (figure 1) that have been reported to be comprised of mucin, fibrin or a mixture of both and can partially or completely obstruct the airways [19, 22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with underlying cardiovascular disease are at risk of developing this condition [1][2][3][4][5]. We present three cases of children with plastic bronchitis after having undergone a Fontan procedure for hypoplastic left ventricle syndrome.…”
Section: Introductionmentioning
confidence: 96%
“…First, a long delay in presenting symptoms of PB after Fontan surgery is unusual [5], as the onset of PB is typically within 1 to 3 years after surgical operation. This finding alerts to regularly evaluate cardiac function and watch over the symptoms of PB in patients who received Fontan intervention.…”
Section: Discussionmentioning
confidence: 99%